Implementing biogas technology as a liquid waste management strategy in palm oil mills to promote a circular economy: Penerapan teknologi biogas sebagai strategi pengelolaan limbah cair di pabrik kelapa sawit untuk mendorong ekonomi sirkular - Agustina, Lya; Suprihatin, Suprihatin; Indrasti, Nastiti Siswi; Prasetya, Hermawan (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2025)
Liquid waste management in the palm oil industry plays an essential role in minimizing environmental impacts and promoting the application of the circular economy concept. This research analyzed effective strategies for liquid waste management through a case study at two palm oil mills in Riau Province. Both mills implemented palm oil mill effluent (POME) treatment technology by converting it into renewable energy in the form of biogas, which was utilized either in biogas power plants (PLTBg) or directly as boiler fuel (co-firing). The results indicated that this technology was effective in reducing environmental impacts, particularly through lowering greenhouse gas emissions, while also improving energy use efficiency in both mills. The applied waste management strategy was based on the principles of reduce, reuse, recycle, and recovery, consistent with the circular economy framework. The environmental, financial, and social benefits derived from this approach are expected to encourage and serve as a reference for the broader adoption of this technology in other palm oil mills, thereby contributing to the realization of a circular economy in the palm oil industry. Keywords: Biogas power plant, circular economy, palm oil mill, POME, wastewater management